دراسة بعض الخصائص البصرية لأغشية أكسيد النيكل(NiO) المطعمة تطعيما مزدوجا بالنحاس(Cu) والكوبالت - زينب, فرحات حميدة; صبرينة, صمامة (universty of elouedجامعة الوادي, 2020)
تضمن هذا العمل دراسة نظرية و تجريبية للخصائص البصرية للأغشية الرقيقة لأكسيد النيكل النقي (NiO) و المطعم تطعيما مزدوجا بالنحاس (Cu) و الكوبالت (Co) بنسبة 6 % نسبا متكاملة، حيث تم ترسيب الأغشية المحضرة على ركائز زجاجية نظيفة تحت درجة حرارة (°500C) بواسطة تقنية الرش بالانحلال الكيميائي الحـراري. حيث أظهر جـهاز التحليل الطيفي للأشعة المـرئية و فوق البـنفسجية (UV-VIS) أن عينة أكسيد النيكل النقية لها نفاذية تقارب (% 77)، و بـعـد التطـعيـم تـزداد لتـصـل إلى (% 98). بينما قيم الفاصل الطاقي للغشاء النقي كانت في حدود (eV 3.69) لكنها قلت بعد التطعيم إذ ترواحت بين (eV 3.42 - 3.61). لقد بلغت طاقة أورباخ للغشاء النقي (0.3860 eV) و بعد التطعيم زادت لتبلغ (eV 0.8190). وجدنا كذلك أن قيم المعاملات: الإنكسار و الخمود و الإمتصاص و التوصيلية البصرية و ثابتي العزل الكهربائي الحقيقي و الخيالي تتأثر جليا باختلاف نسبة التطعيم تبعا للمجال الطاقي خاصة بجوار حافة الامتصاص.This work included a theoretical and experimental study of the optical properties of thin films of pure nickel oxide (NiO) and double doped with copper (Cu) and cobalt (Co) with 6 % integral proportions, the prepared films were deposited on clean glass substrates under a temperature of (500 °C) by the pyrolysis spray technique. Where the visible and ultraviolet (VIS-UV) spectroscopy device showed that a pure nickel oxide sample had a transmittance of about (77 %) and after doping it increases to (98 %). While the values of the gap energy for the pure film were in the range (3.69 eV), but they decreased after doping. It is ranging between (3.42 - 3.61 eV). The Urbach energy of pure film reached (0.3860 eV) and after doping it increased to (0.8190 eV). We also found that the values of the coefficients: refraction, extinction, absorption, optical conductivity, and the real and imaginary dielectric constants are clearly affected by the difference in the doping ratio according to the energy field, especially near the absorption edge.
مذكرة تخرج ماستر فيزياء
Keywords: أغشية رقيقة، أكسيد النيكل، تقنية الرش بالانحلال الكيميائي الحراري، مطيافية (UV-VIS)، التطعيم الثنائي لـ NiO بـ Cu و Co.; thin films, nickel oxide, chemical spray pyrolysis technique, UV-Visible Spectroscopy, Cu and Co codoped NiO.